Application Of The Seven-Box Organizational Diagnosis Model Preziotion To Develop The Organization At PT. Manggala Site Muara Enim - Ilpiyanto, Marko; Wibowo , Wahyu (Universitas Dehasen Bengkulu, 2024)
PT Manggala is a mining service provider company operating in South Sumatra and East Kalimantan which are the two provinces that have the largest coal reserves in Indonesia. The large number of mining service provider companies has made competition as a mining service provider increasingly stringent. Therefore the author raises a research topic entitled